A retrospective study on the geographical distribution of cholera in Limpopo Province, South Africa - Selamolela, S. D. (University of Limpopo, 2016)
Introduction: During mid-November 2008, eleven acute watery diarrhoea cases with the suspicion of cholera like symptoms were detected by a diarrhoea surveillance system at Musina Hospital in Vhembe district - Limpopo Province, South Africa. These cases included eight Zimbabwean and three South African citizens. Laboratory test performed on stool specimens confirmed Vibrio cholerae serogroup 01 Ogawa as the causative pathogen for these reported acute watery diarrhoea cases. Within eight weeks of its onset, the outbreak spread to all the five districts of Limpopo. So far between 15 November 2008 and 01 June 2009, the cumulative number of cases of acute watery diarrhoea reported from five districts of Limpopo Province stands at 4634 including 30 confirmed cholera deaths with an overall case fatality rate of 0.65%. Of these reported cases, Vibrio cholerae has been laboratory confirmed in 656 samples. Methodology: A database was received from the Limpopo Department of Health having all reported cholera cases during the 2008 and 2009 outbreak in Limpopo Province. The data was analysed using STATA statistical software version 12 for windows (STATA Corporation, College Station, Texas). Results: The cholera affected all ages, but the geographic distribution of the disease was very heterogeneous in Limpopo Province. The highest and lowest numbers of cases were reported in Capricorn and Mopani districts, respectively. The majority of the cases 55% (N=2 542) were females. Children less than five years of age 14.2% (N=652) were less affected by the disease. About 73.8% of the cases were aged between O and 44 years. The first four weeks of cholera outbreak strictly included a day-to-day admixture of Zimbabweans and South Africans presenting in the health facilities. The outbreak then affected most South Africans after week five of the epidemic. Conclusion: The cholera outbreak has affected all the five districts of Limpopo Province in South Africa, and new cases continued to be reported until first week of June 2009. There was a link between the Zimbabwean and South African cholera outbreak in Limpopo province.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: Cholera; Diarrahoea; Geographic distribution; Cholera